(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
This study investigated the role of artificial intelligence in the management of university education in Enugu State, Nigeria. Two research questions and two hypotheses guided the study. The study adopted a descriptive survey design. The population comprised the 8,056 lecturers in the Faculty of Education in University of Nigeria, Nsukka and Enugu State University of Technology. A sample of 230 lecturers was drawn using simple random sampling technique. The instrument used for data collection was questionnaire titled ‘role of artificial intelligence in the management of university education questionnaire (RAIMUEQ). The instrument was validated by experts and the reliability was established using Chrombac Alpha Statistics, which yielded an index of 0.91. The findings revealed among others that, the role of artificial intelligence in the management of university education include: streamlining administrative efficiency in the management of education resources, enabling institutions to allocate resources effectively, making decisions on academic matters, analyzing data, creating personalized learning paths, adapting learning contents and materials based on students’ progress, and optimizing resource allocations by predicting future student enrollment. Based on the findings, recommendations were made.